2003
DOI: 10.1161/01.cir.0000053558.55471.2d
|View full text |Cite
|
Sign up to set email alerts
|

Geometric Differences of the Mitral Apparatus Between Ischemic and Dilated Cardiomyopathy With Significant Mitral Regurgitation

Abstract: Background-This study was conducted to elucidate the geometric differences of the mitral apparatus in patients with significant mitral regurgitation caused by ischemic cardiomyopathy (ICM-MR) and by idiopathic dilated cardiomyopathy (DCM-MR) by use of real-time 3D echocardiography (RT3DE). Methods and Results-Twenty-six patients with ICM-MR caused by posterior infarction, 18 patients with DCM-MR, and 8 control subjects were studied. With the 3D software, commissure-commissure plane and 3 perpendicular anteropo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
110
1
2

Year Published

2004
2004
2016
2016

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 320 publications
(124 citation statements)
references
References 31 publications
11
110
1
2
Order By: Relevance
“…[7][8][9][10][11][12][13] Despite this mechanistic complexity, annuloplasty alone produces satisfactory reduction of IMR in up to 80% of cases. 21 This suggests that development of less invasive and safer methods of mitral annuloplasty might afford an important clinical benefit for large numbers of patients with IMR.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…[7][8][9][10][11][12][13] Despite this mechanistic complexity, annuloplasty alone produces satisfactory reduction of IMR in up to 80% of cases. 21 This suggests that development of less invasive and safer methods of mitral annuloplasty might afford an important clinical benefit for large numbers of patients with IMR.…”
Section: Discussionmentioning
confidence: 99%
“…However, mechanisms that underlie these experimental forms of MR may differ from those present in chronic IMR. 10,13,[22][23][24] As for the difference between MR associated with global LV dysfunction and IMR, both MV anatomy 13 and mitral annular geometry 23 were different between them, suggesting potentially different approaches of PTMA in these 2 types of MR. As for the difference between acute and chronic IMR, it was demonstrated that fibrous annular perimeter was dilated and height of the mitral annulus was reduced in ovine models with chronic IMR, whereas they were unchanged in acute IMR. 24 Moreover, it is known that LV dilatation and corresponding mitral annular geometric change after MI play an important role in the production of chronic IMR.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Patients with ischemic MR have more severe LV dysfunction compared with patients without associated MR, and the available data indicate that MR also confers a greater mortality risk and a greater risk of developing overt heart failure (57-60). MR arises in chronic CAD from global and regional LV remodeling (apical and posterior displacement of papillary muscles) leading to papillary muscle displacement, tenting of the mitral valve leaflets, and loss of systolic annular contraction (61)(62)(63). Hence, ischemic MR is primarily a disease of the LV myocardium, and therapies that produce beneficial reverse LV remodeling, such as myocardial revascularization (64), beta-blocker therapy (65), and cardiac resynchronization (66 -68), have the potential to reduce or eliminate MR.…”
mentioning
confidence: 99%